2006
DOI: 10.1348/135532505x68818
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes and attitudes about child sexual abusers: A comparison of experienced and inexperienced professionals in sex offender treatment

Abstract: Purpose. The danger of stereotyping child sex offenders is that such stereotypes allow suspected abusers to avoid detection. The current study investigated whether professionals involved in the treatment of sex offenders endorsed less stereotypes of sex offenders than an ‘inexperienced’ group of teachers. Method. Sixty professionals involved with sex offenders and 71 school teachers completed three questionnaires: the Stereotypes of Sex Offenders Questionnaire; Attitudes Towards Sex Offenders Scale (Hogue, 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 25 publications
7
43
1
6
Order By: Relevance
“…These findings corroborate previous research into attitudes toward sex offenders using different measures (e.g. Hogue, 1993;Kjelsberg & Loos, 2008;Sanghara & Wilson, 2006).…”
Section: Previous Uses Of the Catsosupporting
confidence: 91%
“…These findings corroborate previous research into attitudes toward sex offenders using different measures (e.g. Hogue, 1993;Kjelsberg & Loos, 2008;Sanghara & Wilson, 2006).…”
Section: Previous Uses Of the Catsosupporting
confidence: 91%
“…Firstly, research has identified that experienced professionals (i.e. psychologists involved in sex offender treatment), hold more positive attitudes towards sex offenders compared to individuals with less experience (Hogue, 1993;Sanghara & Wilson, 2006).…”
Section: Limitationsmentioning
confidence: 99%
“…Paedophiles and incest offenders were most feared, and statutory rapists were least feared; however, all types of offenders elicited fear. Sanghara and Wilson (2006) varied the vignettes describing the sex offenders in their study according to the level of endorsements of sex offender stereotypes, and found that those who had the least knowledge about child abuse were more likely to endorse sex offender stereotypes.…”
mentioning
confidence: 99%